A Standard Nomenclature for von Willebrand Factor Gene Mutations and Polymorphisms - Goodeve, A. C.; Eikenboom, J. C. J.; Ginsburg, D.; Hilbert, L.; Mazurier, C.; Peake, I. R.; Sadler, J. E.; Rodeghiero, F. (Thrombosis and Haemostasis, 2001)
Examination of the entire von Willebrand factor (VWF) gene for mutations, particularly in types 1 and 3 von Willebrand disease (VWD) is becoming more widely practised. The sequence of the entire VWF gene will soon be compiled as a single sequence. For these reasons, a clearly defined nomenclature to use for numbering the VWF nucleotide and amino acid sequence is required.The following recommendations are made for VWF numbering. VWF cDNA nucleotide sequence should be numbered from the A of the initiator ATG as the +1 position. Genomic DNA should be prefixed with a “g” and also numbered from this position. Amino acid (aa) numbering should be from the initiator methionine as the +1 position with sequential numbering of aa throughout VWF. To avoid confusion with previously used numbering schemes for mature VWF, which started from serine 764 of pre-pro VWF, the use of the single letter amino acid code is recommended.
Keywords: Standard nomenclature; mutation; polymorphism; recommendation; VWF; VWD